Evaluation of Industrial and Thermal Properties of Mangrove Tree (Rhizophora racemosa) Tannin on Variegated Wood Waste (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
Poor thermal capacity accompanied with deleterious fumes of nitrogen, sulphur and carbon oxides from sawmill wood wastes has led to its decreased utility as domestic energy alternative with consequent environmental implications during combustion at source. This study was undertaken to assess the effect of red mangrove tannin on the thermal capacity of wood waste as potential industrial material for other wood-based products. Tannin extracted from Rhizophora racemosa (red mangrove) bark with methanol (TBM) and water (TBW) as well as leaves with methanol-water (TLMW) were investigated for pH, specific gravity, viscosity, gelation time, total solid content, stain potential, flash point, cold and warm setting times. These were further employed to produce three (3) single-source tannin flaming balls – TBM, TBW and TLMW as well as composite-source types - TBM+TBW, TBM+TLMW and TBW+TLMW using wood-shavings and dust. Flaming balls were engaged to heat up distilled water for 3, 6, 9, 12 and 15 minutes while temperature attained were recorded respectively. Data collected were analysed using analysis of variance (ANOVA) and significant means separated with Duncan Multiple Range Test (DMRT) at 5% level of probability. The results showed that TBM had highest specific gravity (1.80g/cm3), pH (7.60) and Viscosity (2.98poise) while the thermal capacity of the wood-waste was composite TBM+TLMW (100.5 ± 0.63oC) >TBM+TBW> TBW+TLMW compared to sole TBM (90.8oC) > TBW > TLMW > CTR (48.1oC) flaming balls. Thus recommends the need of wood-wastes tannin flaming balls as improvement in the energy sector to combat global warming and mitigate climate change in low-income conurbations.
Keywords: Heating time; Flaming balls; Tannin; Thermal capacity; Wood-waste